Prevalence and diagnostic significance of novel 12-lead ECG patterns following COVID-19 infection in elite soccer players. (3rd October 2022) - Bhatia, R; Malhotra, A; MacLachlan, H; Gati, S; Kasiakogias, A; Marwaha, S; Chatrath, N; Fyyaz, S; Cooper, R; Rakhit, D; Varnava, A; Esteban, M; et al.
Abstract: Background: Identification of athletes with cardiac inflammation following COVID-19 can prevent exercise fatalities. The efficacy of pre and post COVID-19 infection electrocardiograms (ECGs) for detecting athletes with myopericarditis has never been reported. We aimed to assess the prevalence and diagnostic significance of novel 12-lead ECG patterns following COVID-19 infection in elite soccer players. Methods: We conducted a multicentre study over a 2-year period involving 5 centres and 34 clubs and compared pre COVID and post COVID ECG changes in 455 consecutive athletes. ECGs were reported in accordance with the International recommendations for ECG interpretation in athletes. The following patterns were considered abnormal if they were not detected on the pre COVID-19 infection ECG: (a) biphasic T-waves; (b) reduction in T-wave amplitude by 50% in contiguous leads; (c) ST-segment depression; (d) J-point and ST-segment elevation >0.2 mV in the precordial leads and >0.1 mV in the limb leads; (e) tall T-waves ≥1.0 mV (f) low QRS-amplitude in >3 limb leads and (g) complete right bundle branch block. Athletes exhibiting novel ECG changes underwent cardiovascular magnetic resonance (CMR) scans. One club mandated CMR scans for all 28 (6%) athletes, despite the absence of cardiac symptoms or ECG changes. Results: Athletes were aged 22±5 years (89% male and 57% white). 65 (14%) athletes reported cardiac symptoms. The mean duration of illness was 3±4 days. The post COVID ECG was performed 14±16 days following a positive PCR. 440 (97%) athletes had an unchanged post COVID-19 ECG. Of these, 3 (0.6%) had cardiac symptoms and CMRs resulted in a diagnosis of pericarditis. 15 (3%) athletes demonstrated novel ECG changes following COVID-19 infection. Among athletes who demonstrated novel ECG changes, 10 (67%) reported cardiac symptoms. 13 (87%) athletes with novel ECG changes were diagnosed with inflammatory cardiac sequelae; pericarditis (n=6), healed myocarditis (n=3), definitive myocarditis (n=2), and possible/probable myocarditis (n=2). The overall prevalence of inflammatory cardiac sequelae based on novel ECG changes was 2.8%. None of the 28 (6%) athletes, who underwent a CMR, in the absence of cardiac symptoms or novel ECG changes revealed any abnormalities. Athletes revealing novel ECG changes, had a higher prevalence of cardiac symptoms (67% v 12% p<0.0001) and longer symptom duration (8±8 days v 2±4 days; p<0.0001) compared with athletes without novel ECG changes. Among athletes without cardiac symptoms, the additional yield of novel ECG changes to detect cardiac inflammation was 20% (n=3). Conclusions: 3% of elite soccer players demonstrated novel ECG changes post COVID-19 infection, of which almost 90% were diagnosed with cardiac inflammation during subsequent investigation. Most athletes with novel ECG changes exhibited cardiac symptoms. Novel ECGs changes contributed to a diagnosis of cardiac inflammation in 20% of athletes without cardiac symptoms. Funding Acknowledgement: Type of funding sources: None.